Translation strategies of idioms in Shakespeare’s Hamlet into Arabic - Neamah, Hawraa Adil (2019)
The present study seeks to investigate the strategies of translating idioms in Shakespeare’s Hamlet into Arabic. Specifically, it aims to achieve the following objectives: (1) to examine the translation strategies adopted by the Arab translator, Jabra, in rendering idioms in Hamlet into Arabic. (2) To identify the most widely adopted strategy signaling Jabra’s orientation towards domestication or foreignization when rendering idioms in Hamlet into Arabic, and (3) to determine the extent to which Jabra has been able to preserve the communicative equivalence of the translated idioms on the Arab readers. Data of the study comprise 89 English and translated idioms in Arabic, with 11 out of the total number of idioms occurring more than once in the original text of the play, extracted from Hamlet and the Arabic translation of the play. The study employed a qualitative analytical descriptive approach. Baker’s (2011) model on the strategies of translating idioms was utilized for the analysis of idioms in the Target Text (TT). In addition, Newmark’s model to preserve the communicative equivalence (1988) was used to determine Jabra’s success or failure in preserving the communicative equivalence of the translated idioms on the Arab readers. The findings of the study indicate that four out of six of Baker’s strategies were adopted by Jabra when rendering the idioms into Arabic. The most frequent strategy used in the translation of idioms is paraphrasing and the least frequent is the literal strategy which is not under Baker’s model. The tendency towards the adoption of these strategies has characterized the Jabra’s behaviour as orienting towards domestication rather than foreignization, thus bringing the spirit of the source text (ST) closer to the Arab recipients. As for communicative equivalence of the rendered idioms in the Arabic translation, the findings show that Jabra was successful in preserving the effect of the translated idioms on the Arab recipients for the majority of instances, which mainly depict the atmosphere of the play intact. However, in some instances, the communicative equivalence was not preserved, likely due to the cultural differences between English and Arabic. In such cases, the eloquence and poetic sense intended in the source text are lost. These findings suggest that translating idioms require high competency in the source and target languages because of the socio-linguistic and cultural differences which might hinder the transference of such trops into the TL. This competency would facilitate the translator’s task in grasping the connotative meanings of the idioms which are complicated in nature and thus, finding the most suitable equivalent counterparts in the target language in order to retain the embedded meaning of the SL idioms.